2005
DOI: 10.1002/cncr.20900
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen‐treated breast carcinoma patients and the risk of acute myocardial infarction and newly‐diagnosed angina

Abstract: BACKGROUNDIt is known that tamoxifen therapy favorably affects blood cholesterol levels and other cardiovascular disease risk factors; however, to our knowledge, few studies to date have reported a lower risk of heart disease for breast carcinoma patients who are treated with tamoxifen.METHODSA nested, matched, case–control study design was used with data from the General Practice Research Database to examine whether patients with breast carcinoma who had been treated with tamoxifen were at reduced risk of hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 67 publications
1
30
0
1
Order By: Relevance
“…Contrary to results regarding estrogen administration, most, but not all studies of tamoxifen, have shown a positive cardioprotective effect, and none have shown a deleterious effect. 4,35,36 It is of note that a large study on the effects of another selective ER modulator, raloxifene, 37 on cardiovascular outcomes showed no effect, further illustrating the complexity of the interaction between ERactive agents and overall cardiovascular effects. This complexity emphasizes the value of future research in this area as do a number of limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to results regarding estrogen administration, most, but not all studies of tamoxifen, have shown a positive cardioprotective effect, and none have shown a deleterious effect. 4,35,36 It is of note that a large study on the effects of another selective ER modulator, raloxifene, 37 on cardiovascular outcomes showed no effect, further illustrating the complexity of the interaction between ERactive agents and overall cardiovascular effects. This complexity emphasizes the value of future research in this area as do a number of limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…One earlier study reported a protective association between current tamoxifen and the occurrence of treated angina pectoris or myocardial infarction (odds ratio, 0.4; 95% CI, 0.2-0.7; ref. 13). However, this study compared breast cancer patients versus women with other cancers; our large cohort allowed comparison of breast cancer patients on tamoxifen with breast cancer patients not on tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the treatment of breast cancer patients with TAM might be expected to reduce rates of chronic heart disease www.TheOncologist.com compared with placebo. While this cardioprotective effect of TAM has been documented in most trials [62][63][64], it has not been observed in others [3,9,65]. However, two large meta-analyses have confirmed the cardioprotective effects of TAM.…”
Section: Cvdmentioning
confidence: 93%
“…TAM therapy not only improves lipid profiles but also reduces coronary plaques in vivo, reduces C-reactive protein, and modulates nitric oxide production [12,62]. Thus, the treatment of breast cancer patients with TAM might be expected to reduce rates of chronic heart disease www.TheOncologist.com compared with placebo.…”
Section: Cvdmentioning
confidence: 99%